Quality Management Of Educator Resources In The Development Of Inclusion Madrassas In Banten Province - Setiawan, Agung; Priharta, Andry; Arif, Zainal; Bahri, Saiful (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the quality management process of educator resources, identify supporting and inhibiting factors in the quality management process of educator resources towards the development of inclusive madrasas, and analyze strategies in the development of inclusive madrasas in Banten Province. The research method used in this study is a qualitative research method with a case study approach. Data was excavated through participants, namely: madarsah heads, madrasah deputy heads, inclusion teachers, classroom teachers and madrasah operators. The results of this study show that the quality management of educator resources in madrassas is inclusive through the process: planning, recruitment, selection, placement, and evaluation. Supporting factors through cooperation with various related parties, support and policies from the government, as well as the enthusiasm of educators in educating and building inclusive madrasas. The inhibiting factors come from limited funding and the lack of educators with linear educational backgrounds with inclusion madrasah programs. The strategy is to improve the quality of educators by creating a learning week program. The procedures for learning week activities: identifying learning needs, preparing learning program plans, implementing learning activities, evaluating learning outcomes, reflection and follow-up, as well as reporting learning activities. Furthermore, in building a madrasah ecosystem by: visionary madrasah head leadership, creating a teacher learning community, sustainable professional development, infrastructure and technology support, assessment and feedback systems, collaborative and innovative culture, and parents. The implications of this study indicate the importance of educators to continue to improve pedagogic, professional, social, and personality competencies in the context of inclusive madrasas. The implementation of good educator resource management can improve the accessibility and quality of educational services in inclusion madrasas.